SYMBOLIC INTERACTIONISM OF THE MAIN CHARACTER IN THE “NOAH” MOVIE: A SOCIOLINGUISTIC ANALYSIS - Ria, Nurul Miftahurrahmah; Mustikawati, Yunitari; Sahril, Sahril (State University of Makassar, 2024)
This research is entitled